2017
DOI: 10.1149/07711.1825ecst
|View full text |Cite
|
Sign up to set email alerts
|

High Volume Zero Power Low Cost PPB Level Printed Nano-Sensors for IoT

Abstract: The sensing capabilities of carbon nanotubes [CNTs] are often reported in the literature (1,2), but we describe here a commercial sensor based on an amperometric detection method using CNT electrodes. The commercial availability means that it has been vetted not only for sensitivity, but also for practical response time, selectivity, and stability in the temperature, pressure and relative humidity (T, P, RH) and time dimensions. The CNT composite electrodes are robust, and while not as inert as the sp 4 diamo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…Commercially, SPEC Sensors offers printed electrochemical sensors for air quality monitoring. Their sensors appear to exhibit reasonable sensitivity to O 3 (LOD = 0.028 ppm, calculated as 3× the standard deviation of the baseline), CO (<0.250 ppm, from raw data) and NO 2 (0.012 ppm (calculated) and 0.100 ppm (measured)). , The long-term stability (over 8 h), however, is ±0.150 ppm (for O 3 ) which lies above the calculated LOD. This low stability, and the fact that no tests on the influence of changing levels of RH are available, neither from the datasheet nor from publications, makes it hard to estimate the usefulness of these sensors under real-world use cases.…”
Section: Environmentmentioning
confidence: 86%
“…Commercially, SPEC Sensors offers printed electrochemical sensors for air quality monitoring. Their sensors appear to exhibit reasonable sensitivity to O 3 (LOD = 0.028 ppm, calculated as 3× the standard deviation of the baseline), CO (<0.250 ppm, from raw data) and NO 2 (0.012 ppm (calculated) and 0.100 ppm (measured)). , The long-term stability (over 8 h), however, is ±0.150 ppm (for O 3 ) which lies above the calculated LOD. This low stability, and the fact that no tests on the influence of changing levels of RH are available, neither from the datasheet nor from publications, makes it hard to estimate the usefulness of these sensors under real-world use cases.…”
Section: Environmentmentioning
confidence: 86%
“…Alreshaid and Stetter discussed multiple ink-jet-printed nano-sensors for IoT and smart-city applications [ 187 , 188 ]. Mamun et al described various wearable sensors for environmental monitoring for IoT applications [ 189 ]. Long et al demonstrated low-power gas sensing using 3D porous nanostructured metal-oxide sensors for application related to the IoT [ 190 ].…”
Section: Nano-biosensors For Cancer Detection and Future Prospectimentioning
confidence: 99%
“…Ionic liquids (ILs) represent promising media for the next generation of amperometric gas sensors [39][40][41] due to their unique properties such as non-flammability, sufficiently high conductivity, a large electrochemical window, structural modifiability, and excellent thermal stability. It is believed that the negligible volatility of ionic liquids can substantially improve sensor life time; in addition, their electrochemical stability allows the use of a wide range of working electrode potentials for the detection of various target gases.…”
Section: Introductionmentioning
confidence: 99%